2016
DOI: 10.4314/gjpas.v22i2.3
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of the inflorescents of <i>Vernonia calvoana</i> growing in Yakurr Local Government Area of Cross River State, Nigeria

Abstract: Vernonia calvoana is an indigenous green leafy vegetable that grows around the Cameroons and the southern part of Nigeria. This study was designed to evaluate the phytochemical and antioxidant activity of V. calvoana inflorescents using the following methods: 1, 1-diphenyl-2-picrylhydrazyl radical (DPPH), Ferric reducing/antioxidant power (FRAP), 2, 2-azobis-3-ethyl benzothiolin-6-sulphonic acid (ABTS), anti-lipid, superoxide, phosphomolybdate and ascorbic acid assay. The result showed significantly high sapon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
(16 reference statements)
2
6
0
Order By: Relevance
“…This observed activity was dose dependent with significant (P<0.05) activity observed at does level of 400 ug/ml. Findings from this study is consistent with earlier report by Egbung et al (2016), indicating that the inflorescents from V. calvoana possess a high antioxidant activity that is comparable to …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This observed activity was dose dependent with significant (P<0.05) activity observed at does level of 400 ug/ml. Findings from this study is consistent with earlier report by Egbung et al (2016), indicating that the inflorescents from V. calvoana possess a high antioxidant activity that is comparable to …”
Section: Resultssupporting
confidence: 93%
“…Documented reports have shown that extracts from this plant possess hypoglycemic, hypolipidemic, and in vivo antioxidant activity in diabetic animal which could make available the needed information to choose the extract from this plant for further biochemical investigations (Iwara et al, 2015 and2017). Also report by Egbung et al (2016) showed that the inflorescents from the plant possess a strong antioxidant activity compared to ascorbic acid.…”
Section: Introductionmentioning
confidence: 92%
“…The hypolipidemic and antioxidant potentials of V. calvoana leaf extracts in diabetic rats has been reported by Iwara et al (2015) while the in vitro antioxidant properties of the inflorescent of V. calvoana indicated increased concentration of flavonoids (Egbung et al, 2016) thereby supporting its anti-oxidation role as previously reported.…”
Section: Introductionsupporting
confidence: 66%
“…Vernonia calvoana belongs to the Asteraceae family. It is commonly called "Ekeke leaf" and "Uchu nyin" respectively by the indigenes of the central and northern senatorial districts of Cross-River State of Nigeria (Igile et al, 2013, Egbung et al, 2016. The emphasis on Vernonia amygdalina has resulted in the neglect of other less utilised species that may have some ethnomedicinal properties.…”
Section: Introductionmentioning
confidence: 99%
“…Vernonia calvoana has been sparsely investigated compared to other Vernonia species. The anti-oxidant properties of the leaves as well as the inflorescents of Vernonia calvoana has been established (Igile et al, 2013, Egbung et al, 2016. However, there is little or no information on the erythropoietic potentials of the extract of Vernonia calvoana in acetaminophen treated Wistar rats.…”
Section: Introductionmentioning
confidence: 99%